(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The research is out to investigate mind mapping instructional delivery strategy and student academic achievement in science subject in secondary schools in Itu local Government area. Review of related literature was done on mind mapping based instructional delivery strategy and students’ academic achievement, review was also made on gender and students achievement taught with mind map instructional strategy. Quasi experimental design was used for the study. The population of the study was eight hundred and six and a sample size of 100 SS1 students was used. Intact classes were the study sample size. Chemistry achievement test (BAT) was the instrument for data collection. The data collected was analyzed using independent t-test statistical method. The result of the statistical method showed that mind map enhances student achievement in chemistry than lecture method. It was concluded that there is a significant difference in the mean achievement scores of students taught science subject (chemistry) using mind mapping based instructional strategy than those taught using lecture method. Also, there is a significant difference in the mean achievement scores of male and female students taught chemistry with mind map instructional strategy.